Evaluating the effect of information sharing and production control strategies on the performance of supply chains. (6th March 2007) - Krishnan, Shravan K.; Askin, Ronald G.
In this paper, the effect of various system control policies on the performance of a multistage supply chain is studied under a variety of conditions (factors). Three models are considered: pull systems with and without information sharing, and a centralised push system with information sharing. Factors studied include demand distribution, shortage penalty to holding cost ratio at the retailers, ratio of capacity costs at the manufacturer, and demand pattern. Total system costs and variability in production are examined. Improvements due to the use of information and a coordinated push strategy are presented.